THE ROLE OF WAROPEN TRIBAL CHIEF RISEI SAYATI IN THE PROCESS OF RESOLVING CUSTOMARY LAND DISPUTES IN WAROPEN REGENCY - Tanati, Daniel; Yoseph Palenewen, James (Penerbit Lafadz Jaya, 2025)
The research, entitled